Pollen and seed micro-morphology of the genus Polygala (Polygalaceae) in Iran - Sarvi, Ali; Faghir, Marzieh Beygom; Shavvon, Robabeh Shahi (Phytotaxa, 2022)
Pollen and seed micro-morphological features of six species of Polygala distributed in Iran were examined using light (LM) and scanning electron microscope (SEM). The results show a great pollen morphological variation, which provides helpful data for species delimitation in Polygala. The pollen grains are monad, radially symmetrical, isopolar, polyzonocolporate, medium to large, oblate-spheroidal to prolate-spheroidal in shape. We observed four types of surface sculpture (psilate, psilate to granulate, rugulate-granulate and rugulate) and four types of apocolpial area (psilate with small lumina, reticulate with large lumina, micro-perforate and coarsely regulate and gemmate or granulate with lumina). Moreover, the importance of seed micro-morphological traits in species delimitation have demonstrated based on elaiosome appendages size, number of lobes and their sculpture, seed surface sculpture and trichome type.